PATTANI UNITED LIBERATION ORGANIZATION: FROM JIHAD TO LOCAL POLITICS MOVEMENT - Bayu Mitra Adhyatma Kusuma, Theresia Octastefani (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2016)
ABSTRACT In the Kingdom of Thailand, politics and governmental system have close relation with Buddha as official state religion. Moreover Thai government implementing assimilation policy and determine Buddhist Thai as a single national culture and identity. These Thai government autocracy causes the emerged of various resistance group; among other is Pattani United Liberation Organization (PULO) which established in 1968. The research result showed that from the perspective of Thai government, PULO is rebellion, separatist and terrorist. But from the perspective of Malay Muslim in the south, PULO is manifestation of jihad, struggle and heroism. In the beginning, PULO was established in order to fight toward Thai government discrimination toward Malay Muslim in Pattani. But later, PULO’s movement orientation is converted as local politics movement which tries to obtain authority to manage Pattani. Moreover hardly they also try to establish Pattani Darussalam state through political of identity issues for getting public attention. Keywords: PULO, Jihad, Local Politics, Political of Identity ABSTRAK Di Kerajaan Thailand, sistem politik dan pemerintahan memiliki hubungan erat dengan agama Budha sebagai agama resmi negara. Lebih dari itu pemerintah Thailand juga menerapkan kebijakan asimilasi budaya dan menentukan Budha Thailand sebagai budaya dan identitas tunggal nasional. Otokrasi pemerintah Thailand tersebut menyebabkan munculnya berbagai kelompok perlawanan; antara lain Organisasi Pembebasan Pattani Bersatu (PULO) yang didirikan pada tahun 1968. Hasil penelitian menunjukkan bahwa dari perspektif pemerintah Thailand, PULO adalah pemberontak, separatis dan teroris. Tapi dari perspektif Muslim Melayu di selatan, PULO adalah manifestasi dari Jihad, perjuangan dan kepahlawanan. Pada awalnya, PULO didirikan untuk melawan diskriminasi pemerintah Thailand terhadap Muslim Melayu di Pattani. Namun kemudian, orientasi gerakan PULO berubah menjadi gerakan politik lokal yang mencoba mendapatkan kewenangan untuk mengelola Pattani. Lebih dari itu secara lebih keras mereka juga mencoba mendirikan negara Pattani Darussalam melalui isu politik identitas untuk mendapatkan perhatian publik. Kata-kata Kunci: PULO, Jihad, Politik Lokal, Politik Identitas